Perspektif Pendidikan Islam dalam Kitab Waṣaya Al Aba’ Lil Abna’ untuk Membentuk Karakter Santri - Lailatul Shofiyah; Jauharu Ma’arif; Aya Mamu’ah (Edu Journal Innovation in Learning and Education, 2023)
The perspective of Islamic education in the study of the book Waṣãyã Al Ãbã' Lil Abnã' to shape the character of the students, where in the study of the book explains about manners which are transformed into advice about morality. Knowing How the Concept and Implementation of Islamic Education in the Book "Waṣãyã Al Ãbã' Lil Abnã'" To Shape the Character of the Santri, The method used in this research uses a type of Field Research, data collection is done by observation, interview and documentation. This study uses the data analysis model of Hiles and Huberman. The results of this study show that the book Waṣãyã Al Ãbã' Lil Abnã' is a book that is relevant to the formation of the character or morals of students, as seen from the concept of Islamic education in the book as adab seeking knowledge, rights and obligations towards Allah and His Messenger, so that the concept is applied through the activities of the students in the boarding school.